The morphology of argument marking in Zaghawa-Wagi - Isabel Compes (LibraryPress@UF, 2021)
This paper presents an analysis of the system of argument marking on the verb in Zaghawa. Zaghawa, also called Beria in the literature, is a Saharan language of the Nilo-Saharan language phylum spoken in the border region of Sudan and Chad. Like other Saharan languages, it has complex verbal morphology including person indexing. The primary aim of the study is descriptive in that it presents linguistic data of the underdescribed Wagi dialect which is mainly spoken in Sudan. First, the paradigm of bound verbal affixes and their morphology is described. Secondly, one of the functions of the final morpheme of the verb which has not yet been described in detail in previous studies on Zaghawa is analysed. This final morpheme interacts with the person indexes to mark plural participants, and it is exploited to mark a morphological category not yet recognized in the other dialects of Zaghawa: the exclusive/inclusive distinction in the 1st person plural. Therefore, the study provides new data on the Zaghawa verb system and contributes a further detail to our knowledge of the Nilo-Saharan language family.